The influence of the chemical structure on odor qualities and odor thresholds in homologous series of 1,5-alkadien-3-ones, 1-alken-3-ones, 1,5-alkadien-3-ols and 1-alken-3-ols - Lorber, Katja; Schieberle, Peter; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2014)
Odor qualities and odor thresholds in air in homologous series of synthesized alk-1-en-3-ols and alka-1,5-dien-3-ols and their corresponding ketones were evaluated by gas chromatography–olfactometry. In the series of the alk-1-en-3-ols and alk-1-en-3-ones the odor quality changed successively from pungent for the compounds with five carbon atoms via metallic, vegetable-like for the six- and seven-carbon odorants to mushroom-like for the compounds with eight and nine carbon atoms. With further increase in chain length the mushroom-like impression decreased and changed to citrus-like, soapy, or herb-like. In both series, two odor threshold minima were found for the six-carbon and also for the eight- and nine-carbon odorants, respectively. In contrast to this, the odor qualities in the series of the (Z)- and (E)-alka-1,5-dien-3-ols and their corresponding ketones did not change significantly with geranium-like, metallic odors and an increasing mushroom-like odor note with increasing chain length. The lowest thresholds were found for the eight- and nine-carbon (Z)-compounds, respectively.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.theinf
Keywords: vinylketones; gas chromatography−olfactometry; odor threshold